Investigating Data Accessibility of Personal Health Apps - Kim, Yoojung; Lee, Bongshin; Choe, Eun Kyoung (Journal of the American Medical Informatics Association, 2019)
Objective: Despite the potential values self-tracking data could offer, we have little understanding of how much access people have to “their” data. Our goal of this article is to unveil the current state of the data accessibility—the degree to which people can access their data—of personal health apps in the market. Materials and Methods: We reviewed 240 personal health apps from the App Store and selected 45 apps that support semi-automated tracking. We characterized the data accessibility of these apps using two dimensions—data access methods and data types. Results: More than 90% of our sample apps (n ¼ 41) provide some types of data access support, which include synchronizing data with a health platform (ie, Apple Health), file download, and application program interfaces. However, the two approachable data access methods for laypeople—health platform and file download—typically put a significant limit on data format, granularity, and amount, which constrains people from easily repurposing the data. Discussion: Personal data should be accessible to the people who collect them, but existing methods lack sufficient support for people in accessing the fine-grained data. Lack of standards in personal health data schema as well as frequent changes in market conditions are additional hurdles to data accessibility. Conclusions: Many stakeholders including patients, healthcare providers, researchers, third-party developers, and the general public rely on data accessibility to utilize personal data for various goals. As such, improving data accessibility should be considered as an important factor in designing personal health apps and health platforms.